Ultrasonic-Assisted Flavonoid Extraction from Ant Nest - Indriyani, Nita; Goa, Yusnita La; Ely, Muthmainnah; Mendy, Elton (CHEESA: Chemical Engineering Research Articles, 2022)
The extraction of active substances from ant nests can be affected by various extraction methods, whether conventional or sonication. Sample extraction was carried out by maceration and ultrasonic methods with the use of solvents to yield flavonoid compounds. The solvents used were aquadest, 70% ethanol and n-hexane, with a material-to-solvent ratio of 1:50 (w/v). The highest flavonoid content of 14% was obtained by ultrasonic-assisted extraction method, with aquadest as the solvent and at operating conditions of 24 minutes at a temperature of 40oC. Due to their high aquadest solubility and the presence of one or more sulphate ions that are bound to the hydroxyl phenol or sugar, the flavonoids produced are classified as flavonoid sulphate.